2014
DOI: 10.5897/ajmr2013.6565
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of phytase production by Aspergillus japonicus Saito URM 5633 using cassava bast as substrate in solid state fermentation

Abstract: Production of phytase by Aspergillus japonicus URM 5633 was investigated by solid state fermentation (SSF) using cassava bast as substrate. The effects of temperature, pH and initial moisture on phytase production were studied using a full factorial design 2 3 . The maximum phytase activity was 174 U/g dry substrate. The optimum conditions for phytase production were pH 6.5 and 40% initial moisture at 26°C with 96 h of fermentation. A factorial design 2 2 was created to optimise phytase production, where the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…This study found that the degree of pH stability of the precipitated extract obtained from P. adiposa was highly stable within a pH range of 6.0–8.0 and at the low temperature of 4 °C. This result was supported by several previous studies that reported the stability of phytase produced from fungi was influenced by certain conditions such pH and temperature and was dependent upon the fungal species [ 18 , 66 , 88 ]. Salmon et al [ 18 ] reported that phytase produced from S. commune was stable at pH values in a range of 5.0 to 6.0 and at 4 °C.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This study found that the degree of pH stability of the precipitated extract obtained from P. adiposa was highly stable within a pH range of 6.0–8.0 and at the low temperature of 4 °C. This result was supported by several previous studies that reported the stability of phytase produced from fungi was influenced by certain conditions such pH and temperature and was dependent upon the fungal species [ 18 , 66 , 88 ]. Salmon et al [ 18 ] reported that phytase produced from S. commune was stable at pH values in a range of 5.0 to 6.0 and at 4 °C.…”
Section: Discussionsupporting
confidence: 85%
“…The optimum conditions for phytase production from S. commune LPB 101 were achieved at three days of fermentation using wheat bran basal liquid medium at a pH value of 7.0 after being incubated at 33 °C [ 18 ]. Moreira et al [ 66 ] reported on the effective phytase production of A. japonicus URM 5633 in wheat bran using basal liquid medium at a pH value of 6.0 after being incubated at 30 °C for three days. Qasim et al [ 41 ] found that the SSF of A. tubingensis SKA in wheat bran supplemented with basal liquid medium at a pH value of 5.0 after being incubated at 30 °C for 4 days resulted in the highest yield of phytase production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this research was to evaluate the best reaction time, temperature, enzyme concentration and pH to obtain polyphenols for industrial use from green yerba mate, using enzyme-assisted extraction as an alternative to conventional solvent extraction. For this purpose, a factorial experimental design and response surface methodology (RSM) were used, since these have been used as powerful statistical tools for studying the mutual interactions amongst variables over a range of values, while reducing the number of experimental trials (Moreira et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Various filamentous fungi such as Aspergillus sp. (Bhavsar et al 2011;Moreira et al 2014), Mucor racemosus (Bogar et al 2003b), and Sporotrichum thermophile (Singh andSatyanarayana 2006b, Maurya et al 2017), Thermomyces lanuginosus (Makolomakwa et al 2017), and Rhizopus oryzae (Arora et al 2017) have been reported to produce phytase. Several filamentous fungi and their enzyme products are used to break down the bond between the polysaccharides (cellulose and hemicellulose) and lignin in wheat straw to improve its digestibility through the process referred to as biological-pretreatment (Sindhu et al 2016, Choudhary et al 2016, Bagewadi et al 2017.…”
Section: Introductionmentioning
confidence: 99%